Knickpoints and fixed points: the evolution of fluvial morphology under the combined effect of fault uplift and dam obstruction on a soft bedrock river - H.-E. Chen; Y.-Y. Chiu; C.-Y. Cheng; S.-C. Chen; S.-C. Chen (Earth Surface Dynamics)
Rapid changes in river geomorphology can occur after being disturbed by external factors like earthquakes or large dam obstructions. Studies documenting the evolution of river morphology under such conditions have advanced our understanding of fluvial geomorphology. The Dajia River in Taiwan presents a unique example of the combined effects of a coseismic fault (the 1999 Mw 7.6 Chi-Chi earthquake) and a dam. As a result of the steep terrain and abundant precipitation, rivers in Taiwan have exhibited characteristic post-disturbance evolution over 20 years. This study also considers two other comparative rivers with similar congenital conditions: the Daan River was affected by a thrust fault Chi-Chi earthquake as well, and the Zhuoshui River was influenced by dam construction finished in 2001. The survey data and knickpoint migration model were used to analyze the evolution of the three rivers and propose hypothesis models. Results showed that the mobile knickpoint migrated upstream under the influence of flow, while the dam acted as a fixed point, leading to an increased elevation gap and downstream channel incision. Thereby, the narrowing and incision of the Dajia River began at both ends and progressively spread to the whole reach under the combined effects.